Controllable multi-point light focusing of feedback wavefront shaping based on phase superposition Hadamard encoding algorithm - Hu, Yue; Yang, Fan; He, Jiaqi; Ding, Yingchun (Optik (Stuttgart), 2022)
To achieve controllable multi-point light focusing, we develop a new feedback wavefront shaping optimization algorithm called phase superposition Hadamard encoding algorithm (PS-HEA). This algorithm combines the phase superposition method with the Hadamard encoding algorithm, and uniformity coefficient H is introduced to improve the uniformity of multi-point focusing. With the PS-HEA algorithm, we experimentally realized uniform focusing and multi-point customized intensity ratio focusing of light through the scattering medium and demonstrated the strong anti-noise and light control capabilities of PS-HEA in multi-point light focusing. Our research may pave the way for potential applications of optical manipulation and optogenetics.